Ground Profile Recovery from Aerial 3D LiDAR-Based Maps - Sabirova, Adelya; Rassabin, Maksim; Fedorenko, Roman; Afanasyev, Ilya (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2019)
The paper presents the study and implementation of the ground detection methodology with filtration and removal of forest points from LiDAR-based 3D point cloud using the Cloth Simulation Filtering (CSF) algorithm. The methodology allows to recover a terrestrial relief and create a landscape map of a forestry region. As the proof-of-concept, we provided the outdoor flight experiment, launching a hexacopter under a mixed forestry region with sharp ground changes nearby Innopolis city (Russia), which demonstrated the encouraging results for both ground detection and methodology robustness.